The effectiveness of an educational program based on the Brunner model in developing problem solving and mathematical thinking in mathematics for tenth grade female students in the Karak District Education Directorate - Alrawashdeh, Kifaya Barakat; Alsaqarat, Khalaf (Journal of Educational and Psychological Sciences, 2021)
The study aimed to uncover the effectiveness of an educational program based on the Bruner model in developing problem-solving, mathematical thinking and motivation in mathematics among tenth grade students in the Karak Education Directorate, and to achieve the objectives of the study the quasi-experimental approach was used by dividing the study sample into two groups, experimental and control groups, and the study sample consisted of (150) students who were randomly selected, and a set of tests were developed include solve problems test, mathematical thinking test, and motivation questionnaire. The study reached results, the most important of which are: There are statistically significant differences at the level of significance (α≤0.05) in the development of problem solving in mathematics among the tenth grade students in the Directorate of Education of the Karak due to the teaching method, and in favor of the students of the experimental group, and there are statistically significant differences at the level of significance (α≤0.05) in the development of mathematical thinking in mathematics among the tenth grade students in the Directorate of Education of the Karak due to the teaching method, and in favor of the students of the experimental group. In the light of the results, the study recommended that officials in the Ministry of Education should be interested in developing the teaching strategies used in teaching mathematics with a focus on the Brunner model due to its great and positive effect in improving students ’understanding and comprehension of mathematical content.